High-Quality Doped Polycrystalline Silicon Using Low-Pressure Chemical Vapor Deposition (LPCVD). (September 2018) - Padhamnath, Pradeep; Nandakumar, Naomi; Kitz, Buatis Jammaal; Balaji, Nagarajan; Naval, Marvic-John; Shanmugam, Vinodh; Duttagupta, Shubham
Abstract: In this work, analysis of n + and p + doped polycrystalline silicon (poly-Si) layers over in-situ grown interfacial silicon oxide ( iOx ) for use in passivated contact solar cells is presented. Both the poly-Si and the iOx are deposited using an industrial low-pressure chemical vapor deposition (LPCVD) tube furnace. The layers are deposited on planar Czochralski-grown silicon (Cz-Si) wafers and are analyzed for their thickness, in as-deposited and doped conditions. Outstanding surface passivation is demonstrated after n + and p + doping with appropriate capping layer after undergoing high-temperature firing. τeff as high as 15 ms ( n + poly-Si) and 3.1 ms ( p + poly-Si) at an excess carrier density of 1x10 15 cm -3 are obtained. The iVoc values (at 1 sun) are in the range of 745 mV ( n + poly-Si) and 730 mV ( p + poly-Si) and ultra-low J0 values of 1.4 fA/cm 2 ( n + poly-Si) and 7 fA/cm 2 ( p + poly-Si) are obtained.